Ordem no céu, ordem na terra: A revista A Ordem e o ideário anticomunista das elites católicas (1930 1937) - Groppo, Célia Maria (2007)
The present dissertation has a purpose to analyze the bases of Brazilian Catholic s anticommunism, in one of it s biggest age of recrudescence: the third decade of century XX, utilizing as wellspring of information the magazine The Order , which has found in 1921, and was mark in the agglutination of the laic catholic intellectual s elite, as from Jackson de Figueiredo and Dom Vital s Center. The magazine The Order was one the most important vehicles of disclosure of conservation s mind, in its pages was enrolled part of catholic anticommunist s genesis in Brazil, subsiding the construction, rework and dynamism of stereotypes and archetypes about the Church s enemies, in the midst of that, the communism has seen as the most danger of the civilization and the irreconcilable enemy of the Church . The questions in this dissertation search the source of the Catholic s anticommunism in Brazil, among the historic context of its appearance, in the matrixes of conservation s mind, the Catholic s Church position and politician atmosphere in 1930. The limits dates for studying about the magazines articles are placed in the interregnum from 1930, the year which the anticommunist s articles have began to earn space in the magazine, to 1937, the age which is possible to perceive an important change in the ideological directress of the majority of the writers of The Order , under influence of the Humanitarian s Democracy , which was proposal for French s Philosopher Jacques Maritain